Slave trade records from Liverpool, 1754-1792. (East Ardsley, Wakefield, United Kingdom : Microform Academic Publishers, 2008)
These primary sources preserved at the Liverpool Record Office constitute one of the best collections in British archives of private merchants' papers relating to the transatlantic slave trade. Liverpool was the leading slave trading port in the world in the eighteenth century when these documents were compiled. Each individual item has a particular focus, but all illuminate the human and financial aspects of the slave trade. The material includes correspondence with ship captains and Caribbean agents about the acquisition of Africans and their sale; statistics on the Liverpool slave trade; sales accounts of the lots of Africans disembarked in the Americas, often with the names of purchasers and prices; information on dealings with diverse African groups along the coast of West Africa; and details of payments for slave sales. The account books of ships' voyages include material on the outfitting of vessels and the cargoes of goods exported to Africa. Among the items included in this collection are records of the wealthy merchant and banker, Thomas Leyland, who was three times Mayor of Liverpool, and letters by the slave trade captain, John Newton, who later became a clergyman, the composer of the hymn 'Amazing Grace', and a prominent abolitionist. These documents are drawn from papers held at the Liverpool Record Office. Accompanied by an online guide to the collection by Professor Kenneth Morgan, Brunel University. (Included as a supplement to the above are the post-abolition papers of captain and ship-owner, James Brown (ca. 1807-1851), which are held with the main collection at the Liverpool Record Office).
Date range: 1754-1811.
Keywords: Slave trade -- England -- Liverpool -- History -- 18th century